APPLICATION OF BALLOON ANGIOPLASTY OF ARTERIES FOR TREATMENT OF DIABETIC FOOT SYNDROME IN PATIENTS IN BURYAT REPUBLIC - S. Yu. Danilenko; A. N. Plekhanov; P. S. Markevich; T. L. Dashibalova (Acta Biomedica Scientifica)
The report describes experience of treatment of diabetic foot syndrome over the period of 2009-2011. It demonstrates statistic analysis of lesions of arteries of lower extremities, and also frequency of surgical correction of purulent-necrotic lesions of extremities.